Alcohol policy and harm reduction in Australia - Loxley, Wendy; Gray, Dennis; Wilkinson, Celia; Chikritzhs, Tanya; Midford, Richard; Moore, David (Taylor and Francis Ltd, 2005)
With consultations having been held across Australia this year as part of the process of developing a new National Alcohol Strategy, it seemed timely to invite my colleagues from the National Drug Research Institute who are experts in the alcohol field to write this Harm Reduction Digest. The authors have canvassed a range of alcohol policy options and discussed their effectiveness in reducing harm for what is arguably Australia's number one drug problem. Australia's response to alcohol and other drug problems has, historically, been based on 'harm minimization - incorporating supply reduction, demand reduction and harm reduction'. At this time where the policy options for alcohol are being set for the next 5 years in a climate of 'small government', removing restrictions of 'fair competition' in business and a belief in the free market, what does the research have to say about recommended policies and strategies to reduce alcohol-related harm?